2006
DOI: 10.1073/pnas.0603318103
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized signaling of Ras in fission yeast

Abstract: Compartment-specific Ras signaling is an emerging paradigm that may explain the multiplex outputs from a single GTPase. The fission yeast, Schizosaccharomyces pombe, affords a simple system in which to study Ras signaling because it has a single Ras protein, Ras1, that regulates two distinct pathways: one that controls mating through a Byr2-mitogen-activated protein kinase cascade and one that signals through Scd1-Cdc42 to maintain elongated cell morphology. We generated Ras1 mutants that are restricted to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 33 publications
(36 reference statements)
5
119
0
4
Order By: Relevance
“…While the interaction between Ras proteins and a given PAT is selective, some Ras proteins in sc-erf2⌬ budding yeast, as well as in vegetatively growing sp-erf2⌬ fission yeast cells, can still be seen at the PM. We believe that this pool of Ras protein is covalently modified since a Ras1 mutant lacking the cysteine for palmitoylation (C215S) could not be seen at the PM at all (10). It has been shown that palmitoylation can be driven by acyl coenzyme A (CoA) concentration in vitro without PATs (63,64), so we support the idea that this cysteine in Ras proteins could be spontaneously modified to gain PM affinity.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…While the interaction between Ras proteins and a given PAT is selective, some Ras proteins in sc-erf2⌬ budding yeast, as well as in vegetatively growing sp-erf2⌬ fission yeast cells, can still be seen at the PM. We believe that this pool of Ras protein is covalently modified since a Ras1 mutant lacking the cysteine for palmitoylation (C215S) could not be seen at the PM at all (10). It has been shown that palmitoylation can be driven by acyl coenzyme A (CoA) concentration in vitro without PATs (63,64), so we support the idea that this cysteine in Ras proteins could be spontaneously modified to gain PM affinity.…”
Section: Discussionsupporting
confidence: 56%
“…S. pombe has a single Ras protein, Ras1, which controls two evolutionarily conserved pathways that are spatially segregated (9,10). The Ras1-Byr2-mitogen-activated protein (MAP) kinase pathway (11) functions on the PM to mediate mating, while the Ras1-Scd1/Ral1-Cdc42 pathway (12,13) functions in the endomembrane to mediate cell morphogenesis.…”
mentioning
confidence: 99%
“…Despite this dispute over the precise role of intracellular pools of Ras, a recent study using targeted Ras constructs in fission yeast revealed that compartmentalised Ras signalling is evolutionarily conserved. In this case, surface localised Ras supported pathways regulating mating whereas endomembrane Ras supported pathways controlling morphology [100].…”
Section: Compartmentalised Ras Signallingmentioning
confidence: 98%
“…These include preferential isoform coupling to the Raf and phosphoinositide 3-kinase effector pathways and a unique requirement for K-RAS during mouse development (Potenza et al, 2005;Walsh and Bar-Sagi, 2001;Yan et al, 1998). These differences are proposed to be mediated by differential localisation, enabling isoforms to interact with different subcellular pools of effectors and activators (Daniels et al, 2006;Onken et al, 2006;Rocks et al, 2006).…”
Section: Introductionmentioning
confidence: 99%